2021
DOI: 10.3390/en14040841
|View full text |Cite
|
Sign up to set email alerts
|

PV Systems Control Using Fuzzy Logic Controller Employing Dynamic Safety Margin under Normal and Partial Shading Conditions

Abstract: Because of the unpredictable activity of solar energy sources, photovoltaic (PV) maximum power point tracking (MPPT) is essential to guarantee the continuous operation of electrical energy generation at optimal power levels. Several works have extensively examined the generation of the maximum power from the PV systems under normal and shading conditions. The fuzzy logic control (FLC) method is one of the effective MPPT techniques, but it needs to be adapted to work in partial shading conditions. The current p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…PV panels are capable of converting solar irradiation into electricity [10][11][12]. One of the most prominent aspects of PV systems is that they are environmentally friendly and have near zero CO 2 emissions [13][14][15]. In addition, the long-term perspective of PV systems due to their ongoing quality improvement and cost reduction is promising [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…PV panels are capable of converting solar irradiation into electricity [10][11][12]. One of the most prominent aspects of PV systems is that they are environmentally friendly and have near zero CO 2 emissions [13][14][15]. In addition, the long-term perspective of PV systems due to their ongoing quality improvement and cost reduction is promising [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [75] showed (through a simulation case) that FLC combined with P&O is capable of dealing with drifting. In real-time systems, Bakkar et al made an implementation in a commercial PV [76]. In this case, they used a commercial PV with a flyback converter, commonly employed for low power applications [77].…”
Section: Fuzzy Logic Controlmentioning
confidence: 99%
“…Fuzzy logic controllers have been widely used in industrial applications in recent years because of their heuristic nature associated with simplicity, efficiency, and the consideration of its multi-rule variable for the variation of the linear and non-linear parameters of the system [31]. The fuzzy system is composed of a system of rules based on knowledge; the main part of FLC is the knowledge of the base composed of the If-Then rules [32]. Fuzzy Logic is implemented to get the MPP operating voltage point faster with less overshoot; it can also minimize overshoot and the voltage fluctuation after extracting MPPT.…”
Section: Fuzzy Logic Controllermentioning
confidence: 99%
“…Fuzzy logic control has been used power point tracking systems. It is a robust control and does not require the exact information of the mathematical model of the system [32]. The Figure 7…”
Section: Modified Incremental Conductance Algorithmmentioning
confidence: 99%